PERAN BADAN PENASIHATAN PEMBINAAN PELESTARIAN PERKAWINAN (BP4) KUA TERHADAP KEKERASAN DALAM RUMAH TANGGA (KDRT) - Putri Diana; Nur Fitriyana (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2020)
Even though the government issues Law of the Republic of Indonesia Number 23 of 2004 to combat domestic violence cases in Indonesia, those have still happened. In response, the Government religious office (KUA) has founded Marriage Preservation Advisory Board (BP4) in charges to suppress domestic violence. Surveying the community of Kelurahan 10 Ulu, Kecamatan Seberang Ulu II, Palembang, the findings are: First, there are two forms of domestic violence, namely: physical and psychological violence caused by economic factors, lack of knowledge of religion, disobedience of wives to husbands, and lack of understanding of both partners. The two roles of BP4 KUA in carrying out their duties as an advisory body for fostering marriage preservation are: (1) conducting marriage courses every Monday-Wednesday (2) collaborating with RT (Rukun Tetangga) (3) to propagate the Islamic concept of sakinah (tranquility) as part of iman and pious (5) to improve legal consulting services (6) to hold seminars once a year. Also, stages of solving domestic violence cases are (1) coaching (2) research and checking